Effects of macitentan and tadalafil monotherapy or their combination on the right ventricle and plasma metabolites in pulmonary hypertensive rats. (November 2020) - Mamazhakypov, Argen; Weiß, Astrid; Zukunft, Sven; Sydykov, Akylbek; Kojonazarov, Baktybek; Wilhelm, Jochen; Vroom, Christina; Petrovic, Aleksandar; Kosanovic, Djuro; Weissmann, Norbert; Seeger, Werner; Fleming, Ingrid; et al.
Pulmonary arterial hypertension is a severe respiratory disease characterized by pulmonary artery remodeling. RV dysfunction and dysregulated circulating metabolomics are associated with adverse outcomes in pulmonary arterial hypertension. We investigated effects of tadalafil and macitentan alone or in combination on the RV and plasma metabolomics in SuHx and PAB models. For SuHx model, rats were injected with SU5416 and exposed to hypoxia for three weeks and then were returned to normoxia and treated with either tadalafil (10 mg/kg in chow) or macitentan (10 mg/kg in chow) or their combination (both 10 mg/kg in chow) for two weeks. For PAB model, rats were subjected to either sham or PAB surgery for three weeks and treated with above-mentioned drugs from week 1 to week 3. Following terminal echocardiographic and hemodynamic measurements, tissue samples were collected for metabolomic, histological and gene expression analysis. Both SuHx and PAB rats developed RV remodeling/dysfunction with severe and mild plasma metabolomic alterations, respectively. In SuHx rats, tadalafil and macitentan alone or in combination improved RV remodeling/function with the effects of macitentan and combination therapy being superior to tadalafil. All therapies similarly attenuated SuHx-induced changes in plasma metabolomics. In PAB rats, only macitentan improved RV remodeling/function, while only tadalafil attenuated PAB-induced changes in plasma metabolomics.